High-dispersion aluminum nitride ceramic powder for modification and preparation method thereof
By mixing the nano-alumina powder with other modifiers and processing them through multiple steps, a high-dispersion aluminum nitride ceramic powder was prepared, which solved the problem of easy agglomeration of existing aluminum nitride powders and significantly improved the performance of the ceramic substrate.
Patent Information
- Application Number
- CN202411966236.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-29
AI Technical Summary
In industrial production, existing aluminum nitride powders are prone to excessive agglomeration problems caused by mixed uniformity and incomplete nitriding, which affects the strength, thermal conductivity and warping of the ceramic substrate.
The nano-alumina powder with dopamine hydrochloride, trimethylolamide solution, carbon black and dispersant were mixed, and alumina ceramic powder with high dispersion was prepared after stirring, precipitation, filtration, drying, ball milling and carbon heat reduction.
The high dispersion and particle size uniformity of aluminum nitride powder are achieved, the aggregation problem of powder is improved, and the strength, thermal conductivity and warping of the ceramic substrate are improved.
Smart Images

Figure CN119899036A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of inorganic non-metallic powder material preparation, and specifically relates to a highly dispersed aluminum nitride ceramic powder that can be modified and a preparation method thereof. Background Art
[0002] As an ideal heat dissipation material for large-scale integrated circuits and high-power devices, aluminum nitride ceramic substrates have broad application prospects in different fields. If aluminum nitride substrates are to exhibit excellent performance, more stringent requirements must be placed on the raw material aluminum nitride powder. Among them, aluminum nitride powders with fine particle size, high purity, low oxygen content, narrow particle size distribution, and good dispersion are of great significance for the modification of the powder surface and the preparation of high-performance aluminum nitride substrates.
[0003] Most of the aluminum nitride powders currently obtained are high-purity aluminum nitride powders or ultrafine aluminum nitride powders. In industrial production, this type of powder is very prone to problems such as uneven mixing uniformity and incomplete nitridation, which leads to excessive agglomeration of aluminum nitride powders, thereby affecting the strength, thermal conductivity, warping and other properties of the ceramic substrate. Summary of the invention
[0004] The present disclosure aims to solve at least one of the technical problems existing in the prior art and provide a highly dispersed aluminum nitride ceramic powder that can be modified and a preparation method thereof.
[0005] In one aspect of the present disclosure, a highly dispersed aluminum nitride ceramic powder for modification is provided. The highly dispersed aluminum nitride ceramic powder comprises, by weight:
[0006] 100-500 parts of nano-alumina powder;
[0007] 2-10 parts of dopamine hydrochloride;
[0008] 300-800 parts of tris(hydroxymethyl)aminomethane solution;
[0009] 40-200 parts of carbon black;
[0010] 1-5 parts of dispersant.
[0011] Optionally, the particle size of the nano-alumina powder is between 0.3-1.0 μm, and the specific surface area is between 5-9 m 2 / g.
[0012] Optionally, the dispersant is one or more of a cationic dispersant, an anionic dispersant, and a nonionic dispersant.
[0013] Optionally, the cationic dispersant mainly includes one or more of hexadecyl dimethyl ammonium chloride, octadecyl trimethyl ammonium chloride, cationic silicone oil, and dodecyl dimethyl amine oxide;
[0014] The anionic dispersant mainly includes one or more of sodium alkylbenzene sulfonate, sodium alkyl sulfate, sodium fatty acid, and sodium alkyl sulfonate;
[0015] The nonionic dispersant mainly includes one or more of polyoxyethylene amide, polyoxyethylene fatty acid ester, glyceryl monostearate, and sucrose ester.
[0016] Optionally, the concentration of the tris(hydroxymethyl)aminomethane solution is 0.1-0.5 mmol / L.
[0017] Optionally, the content of the nano-alumina powder is 300-500 parts;
[0018] The dopamine hydrochloride content is 5-7 parts;
[0019] The content of the tris(hydroxymethyl)aminomethane solution is 400-600 parts;
[0020] The content of the carbon black is 80-160 parts;
[0021] The content of the dispersant is 2-4 parts.
[0022] The present disclosure provides a method for preparing a highly dispersed aluminum nitride ceramic powder that can be modified as described above, the method comprising:
[0023] The nano-alumina powder and dopamine hydrochloride are put into a tris(hydroxymethyl)aminomethane solution, and the mixture is stirred, settled, filtered and dried in sequence to obtain a surface pretreated alumina powder.
[0024] The alumina powder is put into a ball mill, and then carbon black and a dispersant are added, mixed and stirred to obtain a mixed material;
[0025] Carbothermal reduction synthesis of the mixed material under a nitrogen atmosphere to obtain a nitrided powder;
[0026] The nitrided powder is placed in an air furnace for heat preservation and removal of excess carbon to obtain a highly dispersed aluminum nitride ceramic powder that can be modified.
[0027] Optionally, the nitrogen intake air flow rate is 30-60m 3 / h.
[0028] Optionally, the nano-alumina powder and the dopamine hydrochloride are put into a tris(hydroxymethyl)aminomethane solution and stirred at a speed of 50-100 r / min for 6-12 h.
[0029] Optionally, when the mixed material is subjected to carbon thermal reduction synthesis in a nitrogen atmosphere, the nitrogen inlet gas flow rate is 30-60m3 / h, the multi-stage nitriding sintering process includes: under slightly positive pressure conditions, first heating to 1000°C at a heating rate of 10°C / min, then heating to 1600-1700°C at a heating rate of 3°C / min, and keeping warm for 6h-8h.
[0030] Optionally, the nitrided powder is heated in an air furnace for 2-4 hours, and the insulation temperature is 550° C.-700° C. for 6-12 hours.
[0031] The present disclosure proposes a highly dispersed aluminum nitride ceramic powder that can be modified and a preparation method thereof. The highly dispersed aluminum nitride ceramic powder is made of the following raw material components: 100-500 parts of nano-alumina powder; 2-10 parts of dopamine hydrochloride; 300-800 parts of tris(hydroxymethyl)aminomethane solution; 40-200 parts of carbon black; and 1-5 parts of dispersant. The present disclosure obtains nano-scale aluminum nitride powder with high dispersion by mixing nano-alumina powder with other components to form aluminum nitride powder that is evenly dispersed and completely nitrided, thereby solving the agglomeration problem of nano-scale aluminum nitride powder, which is of great significance for subsequent powder surface modification and improvement of substrate strength, thermal conductivity, warpage and other properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a flowchart of a method for preparing a modified highly dispersed aluminum nitride ceramic powder according to a specific embodiment of the present disclosure;
[0033] Figure 2 This is a scanning electron microscope image of the synthesized aluminum nitride powder of Comparative Example 1 of the present disclosure;
[0034] Figure 3 This is a scanning electron microscope image of the synthesized aluminum nitride powder of Example 1 of the present disclosure. DETAILED DESCRIPTION
[0035] In order to enable those skilled in the art to better understand the technical solution of the present disclosure, the present disclosure is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. It should be understood that the specific embodiments described herein are only used to explain the present disclosure and are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.
[0036] The present invention discloses a highly dispersed aluminum nitride ceramic powder that can be modified. The highly dispersed aluminum nitride ceramic powder is made of the following raw material components by weight: 100-500 parts of nano-alumina powder; 2-10 parts of dopamine hydrochloride; 300-800 parts of tris(hydroxymethyl)aminomethane solution; 40-200 parts of carbon black; and 1-5 parts of a dispersant.
[0037] In this embodiment, dopamine hydrochloride and tris(hydroxymethyl)aminomethane) solution can form a stable and uniform solution. When the alumina raw material is dissolved in the solution, the dopamine hydrochloride therein can perform surface modification on alumina raw materials of different particle sizes, so that the surface of the alumina is coated with a uniform modified layer. The modified alumina raw material has more advantages in material mixing. After high-temperature nitriding reduction, the generated aluminum nitride powder has better dispersibility and more uniform particle size, which provides more possibilities for the subsequent optimization of the hydrolysis resistance of the aluminum nitride powder surface, and effectively improves the strength, thermal conductivity, warping and other properties of the ceramic substrate.
[0038] In some preferred embodiments, the content of nano-alumina powder is preferably 300-500 parts, for example, 300 parts, 350 parts, 400 parts, 450 parts, 500 parts, etc. Of course, in other embodiments, 100 parts, 150 parts, 200 parts, 250 parts, etc. may also be preferred.
[0039] As a further preferred embodiment, the particle size of the nano-alumina powder is between 0.3-1.0 μm, and the specific surface area is between 5-9 m 2 / g.
[0040] It should be understood that the particle size of nano-alumina powder directly affects the packing density and sintering performance of the powder. A smaller particle size means a higher specific surface area, which helps to promote diffusion and reaction between particles during the sintering process, thereby improving the density and strength of the sintered body. However, smaller particle sizes are prone to agglomeration. Therefore, this embodiment adopts nano-alumina powder and synergizes the nano-alumina powder with other modifier components to obtain nano-scale aluminum nitride powder with higher dispersion.
[0041] In other preferred embodiments, the content of dopamine hydrochloride is 5-7 parts, for example, 5 parts, 6 parts, 7 parts, etc. In other embodiments, 2 parts, 3 parts, 4 parts, 8 parts, 10 parts, etc., may also be preferred.
[0042] In this embodiment, dopamine hydrochloride is dissolved in a tris(hydroxymethyl)aminomethane) solution to form a stable and uniform solution, and then the nano-alumina powder is fully stirred in the solution, and the surface of the alumina powder is fully modified and coated by using the strong binding properties of dopamine hydrochloride, so that it is more uniform in the subsequent mixing process with carbon black. After the high-temperature nitridation process, the dopamine hydrochloride on the surface of the alumina is gradually converted into a carbon shell, which can promote carbon thermal reduction while preventing the alumina from agglomerating during nitridation, and can generate aluminum nitride powder with high dispersion and uniform and fine particle size at a relatively low temperature. This kind of powder is of great significance for the subsequent modification of the powder surface, such as hydrolysis resistance, and the improvement of the strength, warping and other properties of the substrate after the powder is subjected to the tape casting process.
[0043] In other preferred embodiments, the content of tris(hydroxymethyl)aminomethane solution may preferably be 400-600 parts, for example, 400 parts, 450 parts, 500 parts, 550 parts, 600 parts, etc., and its concentration is 0.2-0.4mmol / L, for example, 0.2mmol / L, 0.3mmol / L, 0.4mmol / L, etc.
[0044] In other preferred embodiments, the content of carbon black is 80-160 parts, for example, 80 parts, 100 parts, 120 parts, 140 parts, 160 parts, etc. Of course, in other embodiments, 40 parts, 50 parts, 180 parts, 200 parts, etc., may also be preferred.
[0045] In other preferred embodiments, the content of the dispersant is 2-4 parts, for example, 2 parts, 3 parts, 4 parts, etc. Of course, in other embodiments, other weight parts such as 1 part, 5 parts, etc. may also be preferred.
[0046] As a further preferred embodiment, the dispersant is one or more of a cationic dispersant, an anionic dispersant, and a nonionic dispersant.
[0047] As a further preferred embodiment, the cationic dispersant mainly includes one or more of hexadecyldimethylammonium chloride, octadecyltrimethylammonium chloride, cationic silicone oil, and dodecyldimethylamine oxide.
[0048] As a further preferred embodiment, the anionic dispersant mainly includes one or more of sodium alkylbenzene sulfonate, sodium alkyl sulfate, sodium fatty acid, and sodium alkyl sulfonate.
[0049] As a further preferred embodiment, the nonionic dispersant mainly includes one or more of polyoxyethylene amide, polyoxyethylene fatty acid ester, glyceryl monostearate, and sucrose ester.
[0050] like Figure 1 As shown, another aspect of the present disclosure provides a method S100 for preparing the highly dispersed aluminum nitride ceramic powder for modification provided above, comprising specific steps S110 to S140:
[0051] S110, adding nano-alumina powder and dopamine hydrochloride into tris(hydroxymethyl)aminomethane solution, stirring at a speed of 50-100 r / min for 6-12 hours, and then subjecting to sedimentation, filtering and drying to obtain surface pretreated alumina powder.
[0052] Specifically, in parts by weight, the content of nano alumina powder is 100-500 parts, for example, preferably 300-500 parts, the content of dopamine hydrochloride is 2-10 parts, for example, preferably 5-7 parts, the content of tris(hydroxymethyl)aminomethane solution is 300-800 parts, for example, preferably 400-600 parts, and the concentration is 0.1-0.5mmol / L, for example, preferably 0.2-0.4mmol / L.
[0053] In some preferred embodiments, the particle size of the nano-alumina powder is between 0.3-1.0 μm, and the specific surface area is between 5-9 m 2 / g.
[0054] In this embodiment, the surface of the nano-alumina raw material powder and dopamine hydrochloride are pretreated by putting them into a tris(hydroxymethyl)aminomethane solution to form a surface-pretreated nano-alumina powder, wherein after dopamine hydrochloride is dissolved in the tris(hydroxymethyl)aminomethane solution to form a stable and uniform solution, the alumina powder is fully stirred in the solution, and the dopamine hydrochloride component in the solution modifies and coats the surface of the alumina powder, making it more uniform in the subsequent mixing process with carbon black. In addition, after high-temperature nitridation treatment, the dopamine hydrochloride on the surface of the alumina is gradually converted into a carbon shell, which can promote carbon thermal reduction while preventing the alumina from agglomerating during nitridation, and can generate aluminum nitride powder with high dispersion and uniform and fine particle size at a relatively low temperature.
[0055] S120, putting the surface pretreated alumina powder into a ball mill, then adding carbon black and a dispersant, mixing and stirring to obtain a mixed material.
[0056] Specifically, the content of carbon black is 40-200 parts, for example, preferably 80-160 parts, and the content of the dispersant is 1-5 parts, for example, preferably 2-4 parts.
[0057] In some preferred embodiments, the dispersant is one or more of a cationic dispersant, an anionic dispersant, and a nonionic dispersant.
[0058] As a further preferred embodiment, the cationic dispersant mainly includes one or more of hexadecyldimethylammonium chloride, octadecyltrimethylammonium chloride, cationic silicone oil, and dodecyldimethylamine oxide; the anionic dispersant mainly includes one or more of sodium alkylbenzene sulfonate, sodium alkyl sulfate, sodium fatty acid, and sodium alkyl sulfonate; the nonionic dispersant mainly includes one or more of polyoxyethylene amide, polyoxyethylene fatty acid ester, glyceryl monostearate, and sucrose ester.
[0059] In this embodiment, adding carbon black and dispersant to the alumina raw material in a ball mill is conducive to evenly dispersing the carbon black into the nano alumina powder. At the same time, the dispersant prevents the powder from agglomerating, ensuring that the carbon thermal reduction synthesis in the subsequent steps can proceed smoothly, and finally obtaining a nitrided powder.
[0060] S130, loading the mixed material into a graphite crucible, then placing the crucible into a graphite sintering furnace, and performing carbon thermal reduction synthesis under a nitrogen atmosphere to obtain a nitrided powder.
[0061] In some preferred embodiments, the nitrogen inlet gas flow rate is 30-60m 3 / h, and multi-stage nitriding sintering is used during carbon thermal reduction synthesis under nitrogen atmosphere. The specific process is: under slightly positive pressure conditions, the temperature is first raised to 1000℃ at a heating rate of 10℃ / min, and then raised to a holding temperature of 1600-1700℃ at a heating rate of 3℃ / min, and kept at this temperature for 6h-8h. The use of multi-stage nitriding sintering can accurately control the phase composition and microstructure of the material, thereby improving the hardness, strength, warpage and other properties of the material.
[0062] S140, placing the nitrided powder in an air furnace, heating it up and keeping it warm for a period of time, removing excess carbon, and obtaining a highly dispersed aluminum nitride ceramic powder that can be modified.
[0063] Specifically, the nitrided powder is heated in an air furnace for 2-4 hours, the insulation temperature is 550°C-700°C, and the insulation time is 6-12 hours.
[0064] In this embodiment, nano-alumina powder is used as raw material. Through powder surface pretreatment technology, after being fully mixed with carbon black, a highly dispersed aluminum nitride powder that can be modified is synthesized through nitridation and carbon removal processes. Secondly, based on the problem that nano-alumina raw materials are prone to agglomeration and are difficult to mix evenly in the subsequent mixing process, this embodiment uses surfactants to improve the surface properties of the powder, which has a good effect on the mixing of the raw material powders.
[0065] The following will further illustrate the modified highly dispersed aluminum nitride ceramic powder and its preparation method in conjunction with specific examples:
[0066] Comparative Example 1
[0067] This example proposes a method for preparing a modified highly dispersed aluminum nitride powder, comprising the following steps:
[0068] (1) By weight, 100 parts of 0.5 μm alumina powder raw material were put into a ball mill, followed by 40 parts of carbon black, and then 1 part of a cationic dispersant (hexadecyl dimethyl ammonium chloride) were added for ball milling to obtain a mixed material;
[0069] (2) The mixed material is placed in a graphite crucible, and then the crucible is placed in a graphite sintering furnace at 30 min. 3 / h nitrogen inlet flow rate, the temperature was raised to 1000°C at a heating rate of 10°C / min, and then raised to 1650°C at a heating rate of 3°C / min, and kept at this temperature for 8h for carbon thermal reduction synthesis to obtain nitrided powder;
[0070] (3) The nitrided powder is placed in an air furnace, heated to 550°C and kept warm for 12 hours to obtain aluminum nitride powder.
[0071] The scanning electron microscope image of the aluminum nitride powder of this comparative example 1 is as follows Figure 2 As shown in the figure, it can be seen that the particle size of the aluminum nitride powder after carbon thermal reduction is extremely small, but it still has serious agglomeration.
[0072] Example 1
[0073] This example proposes a method for preparing a modified highly dispersed aluminum nitride powder, comprising the following steps:
[0074] (1) by weight, 100 parts of 0.5 μm aluminum oxide and 5 parts of dopamine hydrochloride were added to 400 parts of 0.1 mmol / L tris(hydroxymethyl)aminomethane solution, and stirred at 80 r / min for 6 hours, followed by sedimentation, filtration and drying to obtain a surface pretreated aluminum oxide raw material powder;
[0075] (2) putting the obtained surface pretreated nano-alumina powder raw material into a ball mill, then adding 80 parts of carbon black, and then adding 1 part of cationic dispersant (cationic silicone oil) for ball milling to obtain a mixed material;
[0076] (3) The mixed material is placed in a graphite crucible, and then the crucible is placed in a graphite sintering furnace at 40 m 3 / h nitrogen inlet flow rate, the temperature was raised to 1000°C at a heating rate of 10°C / min, and then raised to 1600°C at a heating rate of 3°C / min, and kept at this temperature for 6h for carbon thermal reduction synthesis to obtain nitrided powder;
[0077] (4) The nitrided powder is placed in an air furnace, heated to 600°C and kept at this temperature for 12 hours to obtain aluminum nitride powder.
[0078] The scanning electron microscope image of the aluminum nitride powder of this embodiment 1 is as follows Figure 3 As shown, the raw alumina powder is modified, and after carbon thermal reduction, the dispersibility of the aluminum nitride powder is significantly improved, which provides more possibilities for the further processing of the aluminum nitride powder.
[0079] By comparing with Comparative Example 1, it can be seen that in Example 1, aluminum nitride powder with good dispersibility can be formed by dissolving aluminum oxide in a stable and uniform solution formed by dopamine hydrochloride and tris(hydroxymethyl)aminomethane solution. In other words, the aluminum nitride powder formed by mixing aluminum oxide with a dispersant and a carbon black component still has agglomeration, which is not conducive to improving the performance of the substrate such as strength and warpage.
[0080] Example 2
[0081] This example proposes a method for preparing a modified highly dispersed aluminum nitride powder, comprising the following steps:
[0082] (1) By weight, 150 parts of 0.8 μm aluminum oxide and 3 parts of dopamine hydrochloride were added to 500 parts of 0.3 mmol / L tris(hydroxymethyl)aminomethane solution, and the mixture was stirred at 80 r / min for 8 hours, then precipitated, filtered and dried to obtain a surface pretreated aluminum oxide raw material powder;
[0083] (2) putting the obtained surface pretreated nano-alumina powder raw material into a ball mill, then adding 40 parts of carbon black, and then adding 2 parts of anionic dispersant (sodium alkylbenzene sulfonate) for ball milling to obtain a mixed material;
[0084] (3) The mixed material is placed in a graphite crucible, and then the crucible is placed in a graphite sintering furnace at 40 m 3 / h nitrogen inlet flow rate, heating to 1000°C at a heating rate of 10°C / min, then heating to 1620°C at a heating rate of 3°C / min, and keeping the temperature for 10h for carbon thermal reduction synthesis to obtain nitrided powder;
[0085] (4) The nitrided powder is placed in an air furnace, heated to 600°C and kept at this temperature for 10 hours to obtain aluminum nitride powder.
[0086] Example 3
[0087] This example proposes a method for preparing a modified highly dispersed aluminum nitride powder, comprising the following steps:
[0088] (1) By weight, 100 parts of 1.0 μm aluminum oxide and 5 parts of dopamine hydrochloride were added to 450 parts of 0.4 mmol / L tris(hydroxymethyl)aminomethane solution, and the mixture was stirred at 70 r / min for 8 hours, then precipitated, filtered and dried to obtain a surface pretreated aluminum oxide raw material powder;
[0089] (2) putting the obtained surface pretreated nano-alumina powder raw material into a ball mill, then adding 40 parts of carbon black, and then adding 3 parts of a non-ionic dispersant (glyceryl monostearate) for ball milling to obtain a mixed material;
[0090] (3) The mixed material is placed in a graphite crucible, and then the crucible is placed in a graphite sintering furnace at 50 m 3 / h nitrogen inlet flow rate, the temperature was raised to 1000°C at a heating rate of 10°C / min, and then raised to 1680°C at a heating rate of 3°C / min, and kept at this temperature for 6h for carbon thermal reduction synthesis to obtain nitrided powder;
[0091] (4) The nitrided powder is placed in an air furnace, heated to 650°C and kept warm for 12 hours to obtain aluminum nitride powder.
[0092] Example 4
[0093] This example proposes a method for preparing a modified highly dispersed aluminum nitride powder, comprising the following steps:
[0094] (1) By weight, 120 parts of 0.3 μm aluminum oxide and 5 parts of dopamine hydrochloride were added to 550 parts of 0.5 mmol / L tris(hydroxymethyl)aminomethane solution, and stirred at a speed of 100 r / min for 8 hours, then precipitated, filtered and dried to obtain a surface pretreated aluminum oxide raw material powder;
[0095] (2) putting the obtained surface pretreated nano-alumina powder raw material into a ball mill, then adding 50 parts of carbon black, and then adding 4 parts of non-ionic dispersant (fatty acid polyoxyethylene ester) for ball milling to obtain a mixed material;
[0096] (3) The mixed material is placed in a graphite crucible, and then the crucible is placed in a graphite sintering furnace at 30 min. 3 / h nitrogen inlet flow rate, the temperature was raised to 1000°C at a heating rate of 10°C / min, and then to 1600°C at a heating rate of 3°C / min, and the temperature was kept for 12h for carbon thermal reduction synthesis to obtain nitrided powder;
[0097] (4) The nitrided powder is placed in an air furnace, heated to 700°C and kept at this temperature for 12 hours to obtain aluminum nitride powder.
[0098] Example 5
[0099] A method for preparing a modified highly dispersed aluminum nitride powder comprises the following steps:
[0100] (1) By weight, 180 parts of 1.0 μm aluminum oxide and 4 parts of dopamine hydrochloride were added to 600 parts of 0.3 mmol / L tris(hydroxymethyl)aminomethane solution, and the mixture was stirred at 80 r / min for 8 hours, then precipitated, filtered and dried to obtain a surface pretreated aluminum oxide raw material powder;
[0101] (2) putting the obtained surface pretreated nano-alumina powder raw material into a ball mill, then adding 50 parts of carbon black, and then adding 1 part of a cationic dispersant (hexadecyl dimethyl ammonium chloride) and 1 part of a non-ionic dispersant (polyoxyethylene amide) for ball milling to obtain a mixed material;
[0102] (3) The mixed material is placed in a graphite crucible, and then the crucible is placed in a graphite sintering furnace at 30 min. 3 / h nitrogen inlet flow rate, the temperature was raised to 1000°C at a heating rate of 10°C / min, and then raised to 1650°C at a heating rate of 3°C / min, and kept at this temperature for 8h for carbon thermal reduction synthesis to obtain nitrided powder;
[0103] (4) The nitrided powder is placed in an air furnace, heated to 550°C and kept warm for 10 hours to obtain aluminum nitride powder.
[0104] Example 6
[0105] This example proposes a method for preparing a modified highly dispersed aluminum nitride powder, comprising the following steps:
[0106] (1) In parts by weight, 150 parts of 0.8 μm aluminum oxide and 5 parts of dopamine hydrochloride were added to 650 parts of 0.5 mmol / L tris(hydroxymethyl)aminomethane solution, and stirred at a speed of 100 r / min for 8 hours, then precipitated, filtered and dried to obtain a surface pretreated aluminum oxide raw material powder;
[0107] (2) putting the obtained surface pretreated nano-alumina powder raw material into a ball mill, then adding 50 parts of carbon black, and then adding 2 parts of anionic dispersant (sodium fatty acid) and 1 part of nonionic dispersant (glyceryl monostearate) for ball milling to obtain a mixed material;
[0108] (3) The mixed material is placed in a graphite crucible, and then the crucible is placed in a graphite sintering furnace at 35 m 3 / h nitrogen inlet flow rate, the temperature was raised to 1000°C at a heating rate of 10°C / min, and then raised to 1680°C at a heating rate of 3°C / min, and kept at this temperature for 12h for carbon thermal reduction synthesis to obtain nitrided powder;
[0109] (4) The nitrided powder is placed in an air furnace, heated to 650°C and kept warm for 12 hours to obtain aluminum nitride powder.
[0110] Example 7
[0111] This example proposes a method for preparing a modified highly dispersed aluminum nitride powder, comprising the following steps:
[0112] (1) By weight, 120 parts of 1.0 μm aluminum oxide and 3 parts of dopamine hydrochloride were added to 550 parts of 0.3 mmol / L tris(hydroxymethyl)aminomethane solution, and stirred at a speed of 60 r / min for 12 hours, followed by sedimentation, filtration and drying to obtain a surface pretreated aluminum oxide raw material powder;
[0113] (2) putting the obtained surface pretreated nano-alumina powder raw material into a ball mill, then adding 60 parts of carbon black, and then adding 1 part of a cationic dispersant (hexadecyl dimethyl ammonium chloride) and 1 part of an anionic dispersant (sodium alkylbenzene sulfonate) for ball milling to obtain a mixed material;
[0114] (3) The mixed material is placed in a graphite crucible, and then the crucible is placed in a graphite sintering furnace at 30 min. 3 / h nitrogen inlet flow rate, the temperature was raised to 1000°C at a heating rate of 10°C / min, and then raised to 1680°C at a heating rate of 3°C / min, and kept at this temperature for 12h for carbon thermal reduction synthesis to obtain nitrided powder;
[0115] (4) The nitrided powder is placed in an air furnace, heated to 650°C and kept warm for 12 hours to obtain aluminum nitride powder.
[0116] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present disclosure, but the present disclosure is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and substance of the present disclosure, and these modifications and improvements are also considered to be within the scope of protection of the present disclosure.
Claims
1. A highly dispersed aluminum nitride ceramic powder that can be modified, characterized in that: The highly dispersed aluminum nitride ceramic powder comprises, by weight: 100-500 parts of nano-alumina powder; 2-10 parts of dopamine hydrochloride; 300-800 parts of tris(hydroxymethyl)aminomethane solution; 40-200 parts of carbon black; 1-5 parts of dispersant.
2. The modified highly dispersed aluminum nitride ceramic powder according to claim 1, characterized in that: The particle size of the nano-alumina powder is between 0.3-1.0 μm, and the specific surface area is between 5-9 m 2 / g.
3. The modified highly dispersed aluminum nitride ceramic powder according to claim 1, characterized in that: The dispersant is one or more of a cationic dispersant, an anionic dispersant, and a nonionic dispersant.
4. The modified highly dispersed aluminum nitride ceramic powder according to claim 3, characterized in that: The cationic dispersant mainly includes one or more of hexadecyl dimethyl ammonium chloride, octadecyl trimethyl ammonium chloride, cationic silicone oil, and dodecyl dimethyl amine oxide; The anionic dispersant mainly includes one or more of sodium alkylbenzene sulfonate, sodium alkyl sulfate, sodium fatty acid, and sodium alkyl sulfonate; The nonionic dispersant mainly includes one or more of polyoxyethylene amide, polyoxyethylene fatty acid ester, glyceryl monostearate, and sucrose ester.
5. The modified highly dispersed aluminum nitride ceramic powder according to claim 1, characterized in that: The concentration of the tris(hydroxymethyl)aminomethane solution is 0.1-0.5 mmol / L.
6. The modified highly dispersed aluminum nitride ceramic powder according to claim 1, characterized in that: The content of the nano-alumina powder is 300-500 parts; The dopamine hydrochloride content is 5-7 parts; The content of the tris(hydroxymethyl)aminomethane solution is 400-600 parts; The content of the carbon black is 80-160 parts; The content of the dispersant is 2-4 parts.
7. A method for preparing the modified highly dispersed aluminum nitride ceramic powder according to any one of claims 1 to 6, characterized in that: The method comprises: The nano-alumina powder and dopamine hydrochloride are put into a tris(hydroxymethyl)aminomethane solution, and the mixture is stirred, settled, filtered and dried in sequence to obtain a surface pretreated alumina powder. The pretreated alumina powder is put into a ball mill, and then carbon black and a dispersant are added, mixed and stirred to obtain a mixed material; Carbothermal reduction synthesis of the mixed material under a nitrogen atmosphere to obtain a nitrided powder; The nitrided powder is placed in an air furnace and subjected to heat preservation treatment to obtain a highly dispersed aluminum nitride ceramic powder that can be modified.
8. The method according to claim 7, characterized in that When the nano-alumina powder and the dopamine hydrochloride are added to the tris(hydroxymethyl)aminomethane solution, the stirring speed is 50-100 r / min and the time is 6-12 h.
9. The method according to claim 7, characterized in that: When the mixed material is subjected to carbon thermal reduction synthesis in a nitrogen atmosphere, the nitrogen inlet gas flow rate is 30-60m 3 / h, under slightly positive pressure conditions, first heat to 1000°C at a heating rate of 10°C / min, then heat to 1600-1700°C at a heating rate of 3°C / min, and keep warm for 6h-8h.
10. The method according to claim 7, characterized in that The nitrided powder is heated in an air furnace for 2-4 hours, kept at 550℃-700℃, and kept for 6-12 hours.
Citation Information
Patent Citations
Aluminum nitride powder and preparation method thereof
CN108689715A
Preparation method of high-performance aluminum nitride material
CN114380279A
Preparation method of high-purity aluminum nitride powder
CN116947502A
Ultrafine aluminum nitride powder preparation process based on high and low temperature carbon thermal reduction method
CN118878333A
Ceramic separation membrane and manufacturing method therefor
WO2024096398A1